Perlindungan Hukum Bagi Pemegang Kartu E-Money Sebagai Alat Pembayaran dalam Transaksi Non Tunai - I Kadek Ary Astrawan; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Fakultas Hukum, Universitas Warmadewa, 2021)
Technological developments have brought changes to payments in the form of cash in the form of conventional metal and paper, which have now developed in the form of electronic payment instruments. One means of payment with an electronic or non-cash system is by using an E-Money card. Through Bank Indonesia Regulation Number 20/6 / PBI / 2018, regulations have been stated regarding the application of consumer protection principles which also regulate the financial loss compensation mechanism but have not clearly and in detail how the compensation mechanism is. In this case there is a blur of norms by the ambiguity of this regulation which causes different interpretations between one institution and another. There are two focuses on this research, about investigation of the legal regulatory mechanism against fund card (E-money) owners in conducting digital transactions and the legal protection mechanism in the event of financial loss due to loss of fund card (E-Money). The research method used in this paper is the normative legal research method, namely researching legal principles and examining written regulations. In conclusion, compensation for E-Money can only be done if it is the damage of the issuer. Banks as electronic money issuers are not responsible for the losses of E-Money owners where this rule violates consumer protection principles.